Photodynamic Therapy in HeLa Cells Incubated with Riboflavin and Pectin-coated Silver Nanoparticles - Rivas Aiello, Maria Belen (2018)
Riboflavin (Rf) is an endogenous photosensitizer, which can participate in Type I and Type II processes. We have recently shown that the yield of the triplet excited states of Rf is enhanced in the presence of pectin-coated silver nanoparticles (Pec@AgNP) due to formation of a complex between Rf and Pec@AgNP (Rf-Pec@AgNP). Consequently, under aerobic conditions, the amounts of singlet molecular oxygen and superoxide radical anion generated are also larger in the presence of the nanoparticles. This result made us suspect that the nanoparticles could have a beneficial effect in Rf-based PDT. To prove this hypothesis, we here compared the photodamage in HeLa cells incubated with Rf in the presence and in the absence of Pec@AgNP applying several optical assays. We used fluorescence imaging of irradiated HeLa cells incubated with Annexin V and propidium iodide to evaluate the occurrence of apoptosis/necrosis, the reduction of the tetrazolium dye MTT to formazan and neutral red uptake to prove cell viability, as well as synchrotron infrared microscopy of single cells to evaluate possible structural changes of DNA and nuclear proteins. The enhanced photodamage observed in the presence of Pec@AgNP seems to indicate that Rf enters into the cells complexed with the nanoparticles.